PENGARUH KOMITMEN ORGANISASI, PERSONAL COST, DAN TINGKAT KESERIUSAN PELANGGARAN TERHADAP KECENDERUNGAN DALAM MELAKUKAN TINDAKAN WHISTLEBLOWING PADA LEMBAGA PERKREDITAN DESA (LPD) SE KECAMATAN MENGWI - Desak Putu Ayu Winda Kristiyani; Ni Putu Ayu Kusumawati; Ni Putu Yeni Yuliantari (UNHI Press, 2021)
Disclosure of fraud (whistleblowing) is the disclosure of violations that can harm the organization by employees or leaders of the organization to third parties who can take action on these violations. This study aims to determine the effect of organizational commitment, personal costs and the level of serious violations on the tendency to take whistleblowing actions at the Lembaga Perkreditan Desa (LPD) in Mengwi sub-district. The population in this study were all employees of the LPD in the Mengwi sub-district, the respondents used were 172 people. The method of determining the sample using the Slovin technique. From the results of this study, organizational commitment, personal cost and the level of seriousness of violations have a positive effect on the tendency to take whistleblowing actions at the Lembaga Perkreditan Desa (LPD) in Mengwi sub-district.